1995
DOI: 10.1249/00005768-199505001-00838
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Branched Chain Amino Acid Supplementation on Indicators of Muscle Damage After Prolonged Strenuous Exercise

Abstract: Abstract:X CHAPTER

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
4
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 156 publications
7
113
4
4
Order By: Relevance
“…Em outro estudo (Coombes, Mcnaughton, 2000) foi avaliado o efeito da suplementação com ACR sobre a concentração sérica de creatina quinase (CK) e lactato desidrogenase (LDH) -parâmetros indicativos de lesão muscular -após a realização de exercício prolongado. Para tanto, 16 homens foram distribuídos em dois grupos, sendo um grupo suplementado com 12 g de ACR por dia, durante 14 dias, juntamente com a dieta normal, e um grupo controle (dieta normal apenas).…”
Section: Exercício De Força Balanço Protéico Muscular E Aminoácidos unclassified
“…Em outro estudo (Coombes, Mcnaughton, 2000) foi avaliado o efeito da suplementação com ACR sobre a concentração sérica de creatina quinase (CK) e lactato desidrogenase (LDH) -parâmetros indicativos de lesão muscular -após a realização de exercício prolongado. Para tanto, 16 homens foram distribuídos em dois grupos, sendo um grupo suplementado com 12 g de ACR por dia, durante 14 dias, juntamente com a dieta normal, e um grupo controle (dieta normal apenas).…”
Section: Exercício De Força Balanço Protéico Muscular E Aminoácidos unclassified
“…Marar et al showed that the administration of fluoxetine to laboratory rats does not significantly affect BUN and creatinine (Marar et al, 1998). Serum CK and LDH are generally known as accurate indicators of muscle damage (Coombes and McNaughton, 2000). CK is present in both skeletal and cardiac muscle and it is released into the blood when myocyte necrosis occurs (Bessman and Carpenter, 1985;Van der Veen and Willebrands, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…BCAA supplementation has been reported to partially suppress the exercise-induced increase in blood creatine kinase activity 27,28) .…”
Section: Increased Amino Acid Breakdown By Exercisementioning
confidence: 99%